A Survey and Exploration on the Organizational Civilization in Iran Governmental Organizations - Mohammadjafar Zarrinnegar; Ali Asghar Fani; Hasan Danaeefard; Jalil Delkhah (مدیریت دولتی, 2018)
The present study seeks to design a model for organizational civilization in governmental organizations. This research is practical in terms of its fundamental purpose and it is mixed-exploratory in nature. The statistical population in the qualitative section includes the experts in human resources and organizational behavior. Purposeful and snowball sampling methods were used to identify the experts. Due to the adequacy of data, 20 experts participated in this study. To test the model, 384 employees of governmental agencies were selected using available method. The data were analyzed using data-driven theory and the structural equation approach. The data were collected through deep interviews along with a 49-item questionnaire. The data-based results indicated the fact that the determination of the goals and leadership of organizational civilization was identified and established in relation to causal circumstances. Regarding the main phenomenon, organizational civilization, and regarding the interventionist conditions, the perfectionist organization was established. The governing body of organizational culture and the desirable actions of empowering human resources management were determined and identified in relation to the main strategy of sociocracy, adhocracy, technocracy, and meritocracy. The main outcome of this model is the civilized organization, and the results obtained from the partial least squares model were approved and the relations were correctly designed.